Sports : the all-American addiction - Gerdy, John R. (Jackson : University Press of Mississippi, 2002)
This book argues that our society's huge investment in organized sports is unjustified. Ardent boosters say that sports embody the "American Way, " developing winners by teaching lessons in sportsmanship, teamwork, and discipline. In fact, Gerdy writes, modern sports are eroding American life and undermining traditional American values essential to the well-being of the nation and its people. Like a drug, this obsession allows Americans to escape problems and ignore issues. Gerdy asks tough questions. Have sports lost their relevance? Is it just mindless entertainment? Is our enormous investment in sports as educational tools appropriate for a nation that needs graduates to compete in the information-based, global economy of the twenty-first century? Do organized sports continue to promote positive ideals? Or, do sports, in the age of television, corporate sky boxes, and sneaker deals, represent something far different? Boldly making his case, Gerdy detects five causes for alarm. A violent, win-at-all-cost mentality exists. A greater number of spectators are idly watching the few elite athletes. An athletic culture that is anti-intellectual systematically creates "dumb jocks." While bridges, inner-cities, and schools are crumbling, tremendous sums of tax dollars vanish to wealthy owners, millionaire players, and to college athletic programs. Studies show that sports are no more effective in promoting equality than any other American institution. Can organized sports be restructured? The author concludes with a series of daring suggestions for change.
Includes bibliographical references (p. 253-258) and index.
Keywords: Sports -- United States; Sports and state -- United States; Sports -- Social aspects -- United States; Sports; Sports -- Politique gouvernementale; Sports -- Aspect social